Melatonin protects against ischemic heart failure in rats - ÖZSAVCI, DERYA; ŞENER, GÖKSEL; AKKİPRİK, MUSTAFA; ÇETİNEL, ŞULE; TETİK, ŞERMİN (WILEY-BLACKWELL, 2013)
Ischemic injury, which occurs as a result of sympathetic hyperactivity, plays an important role in heart failure. Melatonin is thought to have antiatherogenic, antioxidant, and vasodilatory effects. In this study, we investigated whether melatonin protects against ischemic heart failure (HF). In Wistar albino rats, HF was induced by left anterior descending (LAD) coronary artery ligation and rats were treated with either vehicle or melatonin (10 mg/kg) for 4 weeks. At the end of this period, echocardiographic measurements were recorded and the rats were decapitated to obtain plasma and cardiac tissue samples. Lactate dehydrogenase, creatine kinase, aspartate aminotransferase, alanine aminotransferase, and lysosomal enzymes (beta-D-glucuronidase, beta-galactosidase, beta-D-N-acetyl-glucosaminidase, acid phosphatase, and cathepsin-D) were studied in plasma samples, while malondialdehyde and glutathione levels and Na+, K+-ATPase, caspase-3 and myeloperoxidase activities were determined in the cardiac samples. Sarco/endoplasmic reticulum calcium ATPase (SERCA) and caveolin-3 levels in cardiac tissues were evaluated using Western blot analyses. Furthermore, caveolin-3 levels were also determined by histological analyses. In the vehicle-treated HF group, cardiotoxicity resulted in decreased cardiac Na+, K+-ATPase and SERCA activities, GSH contents and caveolin-3 levels, while plasma LDH, CK, and lysosomal enzyme activities and cardiac MDA and Myeloperoxidase (MPO) activities were found to be increased. On the other hand, melatonin treatment reversed all the functional and biochemical changes. The present results demonstrate that Mel ameliorates ischemic heart failure in rats. These observations highlight that melatonin is a promising supplement for improving defense mechanisms in the heart against oxidative stress caused by heart failure.
Keywords: caveolin-3; ischemic heart failure; lysosomal enzymes; Melatonin; LYSOSOMAL-ENZYMES; SKELETAL-MUSCLE; GENE-EXPRESSION; PINEAL-GLAND; ANTIOXIDANT; CAVEOLIN-3; MEMBRANE; DAMAGE; INJURY; MYELOPEROXIDASE